Mythological Narratives in American Cinema and Preparation for the Post-Human World: A Prospective Study from a Linguistic Anthropological Perspective - Al-Timimi, Jawad (Al-Adab Journal, 2024)
Western civilization, led by America and its Anglo-Saxon Protestant cultural structures, is rapidly progressing towards control and possession through military, political, and economic superiority. However, the goal of American civilization is to reshape biological existence, transforming humans into intelligent machines and a combination of human and intelligent machines. This dangerous goal is often ignored by the world’s population. The American political establishment does not prioritize this goal, but shadow institutions, scientific, cultural, and informal studies have been working tirelessly for decades to achieve superior ability to transfer humanity through artificial selection, fulfilling Nietzsche’s dream of reaching the supreme human. America’s shadow foundations are investing in Protestant anthropological linguistics, genetic engineering, and artificial intelligence to reshape human awareness of the world and its future consequences. From a linguistic anthropological standpoint, the study investigates the function of mythical stories in American film and how they prepare audiences for the post-human world. This study aims to uncover the linguistic and anthropological aspects of the anticipated structural disaster that is expected to impact the human race.